(untitled) (Modern education and development, 2025)
Ensuring a company’s financial stability is a key factor for its future success. Therefore, analyzing financial stability serves as the foundation for decision-making by potential investors, buyers, and suppliers. This article discusses the necessity and methodology of analyzing a company’s financial stability. It examines solvency analysis for the near future and financial stability analysis for the long-term perspective.